US Administrations and Morocco from 1974 to 2021: The Double Standards of a Political Machine in Regard to the Western Sahara Conflict - Lourenço, Isabel (The Journal of US Africa -Studies, 2023)
The United States has been instrumental in the Western Sahara conflict through their continuous support to the Kingdom of Morocco and its military occupation of Western Sahara. Even though the support was not always public, given that international law is clear on the status of Western Sahara as Non-Self-Governing Territory, the public USA image, and what we can infer from its confidential correspondence and secret meetings, demonstrate a double standard since 1975, in terminology, speech, and even action. This is further demonstrated by the various presidents’ fickle positions, not always being in accordance with the US Senate and the American Personal Envoys of the Secretary Generals of the United Nations. The goal of this paper is to show the different political stances of the US and their active contribution to the stalemate existing in Western Sahara, by analyzing and synthetizing the political support to Morocco and the influence in the United Nations. Financial and military support will however be excluded from this analysis. Keywords: Morocco, Western Sahara, US politics, US Presidential Office.